REQUEST STRATEGIES IN STUDENTS’ REQUESTIVE EMAILS TO FACULTY: A PRAGMALINGUISTIC ANALYSIS OF POSTGRADUATE STUDENTS’ EMAILS - Hanifah Oktarina; Sinta Dewi; Khoirul Imam; Putri Amanda (Journal of English Education and Linguistics, 2020)
The motivating basis of the study was generated from the fact that there is still little known about the research investigating request strategies in student’s requestive emails in Indonesian context in which the status of English is as a foreign language (EFL). This study intends to examine student’s pragmalinguistic competence realized in request strategies when emailing their lecturers as well as exploring their consideration in choosing certain linguistic means in their email. Case study was employed to get clear description of this particular case. Then, the CCARP framework was utilized to analyze 30 requestive emails composed by 15 students, and qualitative analysis was also applied to draw conclusion from student’s interview. The findings indicated that direct strategies such as mitigated imperative and want statements were mostly realized in more of student’s requestive emails. Moreover, social factors such as age, power, status, and distance become student’s reasons in choosing certain linguistic choices when emailing their lecturers. This present study finally offers some recommendations that can be applied in foreign language setting.